Boundary layer turbulence statistics over transitionally rough marine fouling control coatings. (1st December 2020) - Erbaş, Burcu; Atlar, Mehmet
Abstract: The results of a dedicated boundary layer measurement campaign, which was conducted by using a 2D LDV system over transitionally rough and irregular marine surfaces in a large flow-channel, are presented and discussed in this study. The experimental campaign aimed to investigate the turbulence statistics for zero-pressure gradient turbulent boundary layers developed over marine fouling control coatings, which represent transitionally rough and irregular surfaces, along with hydraulically smooth and fully-rough reference surfaces. A particular emphasis was placed on the wall outer layer similarity. At the same time, the main characteristics of the boundary layer flow such as the velocity defect profiles, Reynolds stresses, triple correlations of turbulence velocities, skewness distributions and flatness factors were comparatively discussed for six different surfaces. The surface roughness properties, boundary layer characteristic parameters, wake parameters and frictional drag properties were also presented for the tested surfaces along with their roughness functions. The outer layer similarity was observed for the surfaces coated with the fouling control coatings in general. The current study presented, perhaps for the first time in such details, the higher-order statistics of turbulence for the turbulent boundary layer flow developed over the state-of-the-art marine fouling control coatings. Highlights: Boundary layer measurements over transitionally rough and irregular marine surfaces in a large flow-channel. Turbulence statistics over marine fouling control coatings, along with reference surfaces. Higher-order turbulence statistics for the state-of-the-art marine fouling control coatings.